The Biology and Pathology of Pseudocaligus uniartus Ho, 2004 (Copepoda: Siphonostomatoida: Caligidae) Infecting Siganids (Siganus sp) in Indonesia - Hilal Anshary; Sriwulan Sriwulan; Ahmad Muyassar (International Journal of Agriculture System, 2013)
Siganids are marine fish which are potentially cultured in ponds or floating net cages. In attempt to produce spawners from wild fish stock, the Caligid Pseudocaligus uniartus appeared in culture facilities causing mild to heavily damage on infected fish. The purposes of this research were to study the mode of infection, biology and pathology of P. uniartus. Egg strings were collected from ovigerous females infecting Siganus guttatus. The parasite posses two nauplius stages, one copepodid, four chalimus stages and young adult. Hatching rates reached 96% at 20 ppt, and 94% and 90% at 25 and 30 ppt, respectively. The eggs started to hatch theree hours after incubation and most eggs had hatched within seven hours. Nauplius stages were estimated for about three hours. Copepodid remained alive after two days without host and started to die within three days and all died within six days. Newly attached copepodid as well as chalimus was mainly found on posterior part of dorsal and anal fins and pectoral fin. Young adult and/or adult parasite were found on the surface of the body, caudal and pectoral fins of host. The estimated time needed from copepodid to adult was seven days. All larvae have become adults on day 10. The complete life cycle was estimated within 7.6 - 10.6 days. Heavily infected fish showed lesion on skin and eroded fins. Large number of inflammatory cells was infiltrated on the infected areas.